2020
DOI: 10.1186/s40659-020-00310-6
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressive function of Matrin 3 in the basal-like breast cancer

Abstract: Background Basal-like breast cancer (BLBC) or triple-negative breast cancer (TNBC) is an aggressive and highly metastatic subtype of human breast cancer. The present study aimed to elucidate the potential tumor-suppressive function of MATR3, an abundant nuclear protein, in BLBC/TNBC, whose cancer-relevance has not been characterized. Methods We analyzed in vitro tumorigenecity by cell proliferation and soft agar colony formation assays, apoptotic cell death by flow cytometry and Poly (ADP-ribose) polymerase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 48 publications
3
11
0
Order By: Relevance
“…We proceeded to choose the concentration point closest to the IC 50 value (12.5 µg/mL PSI-LHCI, *** p < 0.01) revealed after exposure of MDA-MB-231 cells to PSI-LHCI following 24 h of incubation. Our results confirmed that PSI-LHCI induces a decrease in cell viability in the triple-negative breast cancer cell line, MDA-MB-231, with superior results than the well-known cancer cell line positive control Staurosporine [47].…”
Section: Cellular Internalization Studies Of Psi-lhci In Mda-mb-231 C...supporting
confidence: 82%
See 1 more Smart Citation
“…We proceeded to choose the concentration point closest to the IC 50 value (12.5 µg/mL PSI-LHCI, *** p < 0.01) revealed after exposure of MDA-MB-231 cells to PSI-LHCI following 24 h of incubation. Our results confirmed that PSI-LHCI induces a decrease in cell viability in the triple-negative breast cancer cell line, MDA-MB-231, with superior results than the well-known cancer cell line positive control Staurosporine [47].…”
Section: Cellular Internalization Studies Of Psi-lhci In Mda-mb-231 C...supporting
confidence: 82%
“…A prestained protein standard was used to estimate PSI-LHCI and co-eluting components (~3.5-260 kDa). Two-dimensional (2D) native/SDS-PAGE polypeptide spots indicated a high abundance of PSI-LHCI complex components and subunits as observed in previous reports providing an assessment of the polypeptide composition of our preparation [28,47]. Although we notice a small contribution of LHCII, a mobile antenna, judging from our 77 K fluorescence assay, it is not deemed a major contributor [34,35].…”
Section: Psi-lhci Polypeptide Composition Analysis By Sds-page and Bn...supporting
confidence: 76%
“…Other studies also observed that Matrin3 loss results in reduced cell proliferation 24,25,46 and suggested increased apoptosis as a cause. Our data indicate that at least in CRC cells, Matrin3 depletion results in alterations in microtubule dynamics, possibly leading to reduced cell proliferation as studies had shown that the stabilization of microtubules inhibit cell proliferation [47][48][49] .…”
Section: Discussionmentioning
confidence: 81%
“…The impaired formation of dynamic nuclear condensates due to ALS-associated mutations in Matrin3 possibly contributes to its pathogenic mechanism 22 . There is conflicting evidence for a role of Matrin3 in cancer with some studies indicating a potential role of Matrin3 as an oncogene and other studies suggesting a tumor suppressive function [23][24][25] . Although many different Matrin3 RNA targets were catalogued [11][12][13] , it remains unclear which of these specific targets mediate Matrin3 function and contribute to the observed phenotypes of Matrin3 in different cells and tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Western blotting was performed as described [ 52 ]. The cells were lysed in RIPA buffer supplemented with protease and phosphatase inhibitors (GenDepot, Houston, TX, USA).…”
Section: Methodsmentioning
confidence: 99%